Globally altered epigenetic landscape and delayed osteogenic differentiation in H3.3-G34W-mutant giant cell tumor of bone - Pavlo Lutsik; Annika Baude; Daniela Mancarella; Simin Öz; Alexander Kühn; Reka Toth; Joschka Hey; Umut H. Toprak; Jinyeong Lim; Viet Ha Nguyen; Chao Jiang; Anand Mayakonda; et al. (Nature Communications, 2020)
The histone variant mutation H3.3-G34W occurs in the majority of giant cell tumor of bone (GCTB). By profiling patient-derived GCTB tumor cells, the authors show that this mutation associates with epigenetic alterations in heterochromatic and bivalent regions that contribute to an impaired osteogenic differentiation and the osteolytic phenotype of GCTB.